Prices for veterinary care of dogs, cats and horses in selected countries in Europe - Egenvall, Agneta; Höglund, Odd V.; Hoffman, Ruben; Valle, Paul S.; Andersen, Pia Haubro; Lönnell, Cecilia; Byström, Anna; Bonnett, Brenda N. (Frontiers in Veterinary Science, 2024)
In recent years, prices for veterinary care have received considerable attention in mainstream media, yet scientific literature has not delved into actual figures. This study aims to elucidate veterinary care costs for dogs, cats, and horses across five countries (Sweden (SE), Norway (NO), Denmark (DK), United Kingdom (UK), and Ireland (IR, with limited data)) through web searches. Utilising online business directories, we located URLs featuring veterinary care prices in autumn 2022, and repeated tri-monthly five times. Vetpris.se (VP), a price comparison site for SE, NO, and DK, emerged from the search. Additionally, we sought to compare price data from veterinary clinics (ranging from animal hospitals to small private clinics) using a similar approach to VP. We targeted elective procedures (e.g., gonadectomy, GDY) and common procedures (e.g., pyometra surgery in dogs). Comparing data from the same clinics' websites and from VP within extraction from autumn 2022 to winter 2023/2024, median prices for dog and cat GDY were largely consistent. By October 2023, median prices for male cat GDY ranged from €72 (SE) to €230 (DK), and €130 (SE) to €361 (DK) for females; for dog GDY from €390 (SE) to €599 (DK) for males, and €461 (UK) to €1015 (DK) for females. Across sources, median prices for cat and dog GDY increased by 2-24% over a year for procedures with at least 10 clinics per extraction. Equine GDY (per sedation and local analgaesia) in SE saw a 64% increase by year-end, with a median price of €492. Emergency surgeries during regular-hours (e.g., pyometra and caesarean section) in SE were approximately €2300 at the last extraction, marking a 27% increase for pyometra surgery during regular-hours and 15% after-hours compared to the previous year. Variability existed within and across countries and diagnoses/procedures. Cross-validation suggested VP generally provided reliable information, though data points for emergencies were limited. Our web searching tool necessitated extensive manual verification, indicating room for further development. We recommend enhancing price transparency for animal owners to become better informed about the cost of veterinary care and be able to make informed choices.